2016
DOI: 10.1155/2016/6143126
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Boltzmann Model of 3D Multiphase Flow in Artery Bifurcation Aneurysm Problem

Abstract: This paper simulates and predicts the laminar flow inside the 3D aneurysm geometry, since the hemodynamic situation in the blood vessels is difficult to determine and visualize using standard imaging techniques, for example, magnetic resonance imaging (MRI). Three different types of Lattice Boltzmann (LB) models are computed, namely, single relaxation time (SRT), multiple relaxation time (MRT), and regularized BGK models. The results obtained using these different versions of the LB-based code will then be val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…Careful comparison and mutual validation of those two methods have been done previously. 14,34 Despite that FVM and LBM are using different mathematical frames, highlyaccurate simulation results always require long period of computational time. For FVM, this means highlyaccurate mathematical scheme, large number of computational cells and complicated fluid models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Careful comparison and mutual validation of those two methods have been done previously. 14,34 Despite that FVM and LBM are using different mathematical frames, highlyaccurate simulation results always require long period of computational time. For FVM, this means highlyaccurate mathematical scheme, large number of computational cells and complicated fluid models.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, as an alternative to FVM, LBM is also applied for haemodynamic simulations. [14][15][16] Previous comparison of LBM and FVM in the haemodynamic simulation of a bifurcation in abdominal arteries confirmed that LBM is able to deliver comparable accurate results with less computational cost. Furthermore, the lattice generation process is much easier than FVM grid generation.…”
Section: Introductionmentioning
confidence: 87%
“…Applications of the LBM are now found in a wide range of disciplines including physics, chemistry, materials, biomedicine and various branches of engineering. Xia et al (2017) used LBM for modeling viscoacoustic wave propagation, Abas et al (2016) simulates and predicts the laminar flow inside the 3D aneurysm geometry, van den Akker (2018) present review about the Lattice Boltzmann simulations for multi-scale chemical engineering, Svyetlichnyy et al (2018) modeling of additive layer manufacturing. The dendritic growth during solidification of Al-Cu alloys under forced and natural convection was simulated by Eshraghi et al (2017).…”
Section: Hybrid Lattice Boltzmann Methods and Cellular Automata Model...mentioning
confidence: 99%
“…Applications of the LBM are now found in a wide range of disciplines including physics, chemistry, materials, biomedicine and various branches of engineering. Xia et al (2017) used LBM for modeling viscoacoustic wave propagation, Abas et al (2016) simulates and predicts Eshraghi et al (2017). LBM simulates the dynamics of "pseudoparticles" constrained to move and collide with each other on a structured lattice, so it can be applied for modeling of different variants of flows involving highly complex, multiply-connected domains, as well as phase transformations in flows.…”
Section: Hybrid Lattice Boltzmann Methods and Cellular Automata Model...mentioning
confidence: 99%
“…This method is not yet popular for computational hemodynamics and no commercially-available software that uses the lattice Boltzmann equation to analyze hemodynamics of cerebral aneurysms has been established. Only a few authors have reported their experiences with hemodynamic simulation for cerebral aneurysms by applying the lattice Boltzmann equation using their in-house code 24,25 . Their conclusions were that LBM could be considered an alternative solver for computational hemodynamics of cerebral aneurysms.…”
Section: Significance Of Cfd Analysis From Tof-mramentioning
confidence: 99%